Development of metal-doped zinc ferrite magnetic sensor material from steel dust waste - Tan, Jian Bin (2022)
The steel dust, EAFD is a by-product from steel production. EAFD stands for electric-arc furnace dust. The amount of EAFD will continue to rise due to the growing demand for steel. The composition of the EAFD contains valuable metal elements, including Zn, Fe, Ca and Mn. Nevertheless, the EAFD is a hazardous solid waste due to its heavy metal elements. To date, researchers have managed to recover zinc from the EAFD through hydrometallurgical and pyrometallurgical processes. However, these processes produce waste. A different approach is required to transform the EAFD into a green product. Thus, the project’s main aim is to develop the nickel zinc ferrite magnetic sensor material from the steel dust waste. Solid state reaction was applied to synthesize the Ni-Zn ferrite. The mixture of treated EAFD and nickel(II) chloride hexahydrate (NiCl2.6H2O) was sintered at 1100 °C for two hours with the mass ratio R(TE/N) of 6:4 and 8:2. The R(TE/N) is the mass ratio of treated EAFD to nickel(II) chloride hexahydrate. The synthesized Ni-Zn ferrite with the R(TE/N) of 6:4 has the magnetization (Ms) of 61.24 emu/g, coercivity (Hci) of 21.654 G, and retentivity (Mr) of 2.1941 emu/g. The synthesized nickel zinc ferrite with the R(TE/N) of 8:2 has Ms, Hci and Mr of 47.372 emu/g, 6.4347 G, and 0.57649 emu/g respectively. The Ni-Zn ferrite is a soft magnetic material. Hence, it can be used to develop magnetic sensors for high frequency applications (above 1MHz) in 5G technologies.